Morphological and morphometric anatomy of the lesser occipital nerve and its possible clinical relevance - Latif Saglam; Osman Coskun; Ozcan Gayretli (Scientific Reports, 2024)
Abstract The lesser occipital nerve (LON) has one of the most variations among occipital nerves. We aimed to investigate morphological and morphometric features of LON. A total of 24 cadavers, 14 males (58%) and 10 females (42%), were dissected bilaterally. LON was classified into 3 types. The number of branches and the perpendicular distances of the point where LON emerged from the posterior border of sternocleidomastoid muscle to vertical and transverse lines passing through external occipital protuberance were determined. The shortest distance between LON and great auricular nerve (GAN), and linear distance of LON to its branching point were measured. The most common variant was Type 1 (30 sides, 62.5%), followed by Type 2 (12 sides, 25%) and Type 3 (6 sides, 12.5%), respectively. In males, Type 1 (22 sides, 78.6%) was the most common, while Type 1 (8 sides, 40%) and Type 2 (8 sides, 40%) were equally common and the most common in females. On 48 sides, 2–9 branches of LON were observed. The perpendicular distance of said point to vertical and transverse lines was meanly 63.69 ± 11.28 mm and 78.83 ± 17.21 mm, respectively. The shortest distance between LON and GAN was meanly 16.62 ± 10.59 mm. The linear distance of LON to its branching point was meanly 31.24 ± 15.95 mm. The findings reported in this paper may help clinicians in estimating the location of the nerve and/or its branches for block or decompression surgery as well as preservation of LON during related procedures.